Social demography and pandemics - Dommaraju, Premchand (2021)
All the three components of demographic change—births, deaths, and migration—are deeply affected by pandemics. While deaths are the most obvious, pandemics leave an imprint, over the short and long term, on all the three demographic components. The demographic impacts are social in the sense that different social groups are impacted differently. Social demography is useful to uncover and understand social aspects of population dynamics including issues related to inequality, inequity, and differentials in demographic outcomes. In this commentary, I reflect on the social demographic implications of COVID-19 pandemic (the pandemic from now on) in Asia